Extracellular Hsp90α Supports the ePKM2-GRP78-AKT Axis to Promote Tumor Metastasis - Zhang, Shaosen; Wang, Caihong; Ju, Jiujun; Wang, Caixia (Frontiers in Oncology, 2022)
Tumor-secreted proteins can provide numerous molecular targets for cancer diagnosis and treatment. Of note, pyruvate kinase M2 (PKM2) is secreted by tumor cells to promote malignant progression, while its regulatory mechanism or the interacting network remains uncovered. In the present study, we identified extracellular heat shock protein 90 alpha (eHsp90α) as one potential interacting protein of ePKM2 by mass spectrometry (MS), which was further verified by pull-down and co-immunoprecipitation analysis. Later, we found that eHsp90α enhanced the effect of ePKM2 on migration and invasion of lung cancer cells. Blocking of Hsp90α activity, on the other hand, attenuated tumor migration or invasion induced by ePKM2. Eventually, the in vivo role of Hsp90α in regulating ePKM2 activity was validated by the mouse xenograft tumor model. Mechanistically, we found that eHsp90α binds to and stabilizes ePKM2 to protect it from degradation in the extracellular environment. Besides, eHsp90α promoted the interaction of ePKM2 with cell surface receptor GRP78, which leads to the activation of the ePKM2/GRP78/AKT axis. Collectively, we unraveled the novel molecular mechanism of eHsp90α in regulating ePKM2 activity during tumor progression, which is beneficial for the development of new treatments against lung cancer.